2015
DOI: 10.5005/jp-journals-10024-1773
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam Computed Tomography Evaluation of Root Canal Preparation using Various Rotary Instruments: An in vitro Study

Abstract: Aim:To evaluate the remaining dentin thickness of teeth after cleaning and shaping the root canal using three rotary instrumentation technique using cone-beam computed tomography (CBCT). Materials and methods:This in vitro study is being done with 30 premolar samples with 20' curvature. The study is divided into three groups a CBCT was taken to measure the shortest distance from the root canal outline to the closest adjacent root surface was measured at each level from the cementoenamel junction (CEJ) (1,3, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 19 publications
1
60
0
1
Order By: Relevance
“…This is contradictory to the indings of Banga et al, which suggests that the most commonly treated tooth was 36, followed by 46 (Banga et al, 2018). This (Ramamoorthi et al, 2015) could be because of the difference (Ramanathan and Solete, 2015) in age selection (Ravinthar and Jayalakshmi, 2018) of the sample and the difference in sample size (Rajendran et al, 2019). There is also a statistically signi icant (p<0.05) association between age and the incidence of dental caries in the mandibular irst molars.…”
Section: Resultsmentioning
confidence: 63%
“…This is contradictory to the indings of Banga et al, which suggests that the most commonly treated tooth was 36, followed by 46 (Banga et al, 2018). This (Ramamoorthi et al, 2015) could be because of the difference (Ramanathan and Solete, 2015) in age selection (Ravinthar and Jayalakshmi, 2018) of the sample and the difference in sample size (Rajendran et al, 2019). There is also a statistically signi icant (p<0.05) association between age and the incidence of dental caries in the mandibular irst molars.…”
Section: Resultsmentioning
confidence: 63%
“…The in-vitro studies conducted at our university includes (Ramanathan and Solete, 2015;Rajendran et al, 2019;Janani et al, 2020), the invivo studies include (Nasim and Nandakumar, 2018;Siddique, 2019), the molecular study (Ramesh et al, 2018;Noor and Others, 2016), the reviews and systematic reviews published are (Kumar and Antony, 2018;Ravinthar and Jayalakshmi, 2018;Rajakeerthi and Ms, 2019), the surveys conducted (Manohar and Sharma, 2018;Jose et al, 2020), and the clinical trial conducted on root canal irrigants were (Teja and Ramesh, 2019;Ramamoorthi et al, 2015). Currently, we are analyzing retrospective studies.…”
Section: Data Collection/tabulationmentioning
confidence: 99%
“…Various studies have shown that the survival chance of the pulp with the accidental exposure of the pulp during the time of tooth preparation was high (Ramanathan and Solete, 2015) rather than due to the progression of caries (Janani et al, 2020). The main reason for this is due to the bacterial invasion into the pulp on caries exposure (Kumar and Antony, 2018).…”
Section: Introductionmentioning
confidence: 99%